STUDI TENTANG KOMPLEKS MAKAM SYEKH JANGKUNG DI DUKUH LANDOH DESA KAYEN KECAMATAN KAYEN KABUPATEN PATI - Mulyani, Hayuntri (Candi, 2013)
The objective of research is to find out: (1) the history of Syekh Jangkung; (2) cultural elements contained within the building complex of the tomb of Syekh Jangkung; (3) form of ritual pilgrimage at the tomb of Syekh Jangkung; (4) Effect of pilgrimage at the tomb complex activity Syekh Jangkung towards socio-economic communities. Based on the results of research can be concluded: (1) Saridin the son of Ki Ageng Keringan named Syed Abdullah 'Asyiq with Sujinah/ Dewi Samaran. Saridin is the first name of Syekh Jangkung. (2) cultural elements contained in the tomb complex of Syekh Jangkung buildings include: a). gate with paduraksa shaped and briefly temple; b). Pendopo is have a roof form joglo; c). Dome-shaped house joglo covered with lotus flowers; d). incorporating mosque with roasted panggang pe roof. (3) Form of ritual pilgrimage at the tomb of Syekh Jangkung begins with the sowing of flowers and burning incense by the officer taking the tomb and ends with "Tirto Usodo" by pilgrims. (4) Effect of activity on the complex journey to the tomb of Syekh Jangkung socio-economic communities is a). the social field can change the way people dress around, can increase the sense of kinship and mutual cooperation; b). the economy is creating jobs that can reduce unemployment. Keywords: Syekh Jangkung, architecture, pilgrimage